222Rn Exhalation Rate of Building Materials: Comparison of Standard Experimental Protocols and Radiological Health Hazard Assessment - Francesco Caridi; Lorenzo Pistorino; Federica Minissale; Giuseppe Paladini; Michele Guida; Simona Mancini; Domenico Majolino; Valentina Venuti (Applied Sciences)
This study evaluates the accuracy of 222Rn exhalation rates from building materials using two standard experimental protocols, thus addressing the increasing importance of rapid radon assessment due to health concerns and regulatory limits. In detail, six types of natural stones frequently employed for the construction of buildings of historical-artistic relevance were analyzed using the closed chamber method (CCM) combined with the Durridge Rad7 system, by using two experimental protocols that differed in the measurement duration: 10 days (Method 1) versus 24 h (Method 2). Obtained results revealed that the radon exhalation rates ranged from 0.004 to 0.072 Bq h−1, which are moderate to low if compared to studies in other regions. Statistical comparison using the u-test confirmed equivalence between protocols (u-test ≤ 2), thus supporting the validity of the faster Method 2 for practical applications. Furthermore, to estimate the potential indoor radon levels and determine the associated radiological risks to human health, for the investigated natural stones, the Markkanen room model was employed. As a result, simulated indoor radon concentrations remained well below regulatory thresholds (maximum value: 37.3 Bq m−3), thus excluding any significant health concerns under typical indoor conditions.